Development of a PLC Based Automation Cell for Industry - Arafath Al Fahim; Mohammad Mizanur Rahman; Monowar Wadud Hridoy; Kazi Riad Uddin (Journal of Integrated and Advanced Engineering (JIAE), 2023)
In recent years there is a considerable growth and development of automation mainly in industrial sectors. This technological revolution is quickly reducing the need of humans to operate machines. To reduce cost and increase the production rate every industry tries to invent new technology. Bringing automation in the industrial sector is one of them. Automation in the industrial sector reduces human effort, makes the system smooth and also increases productivity. For this tendency every industry wants to design an automatic production process with minimal amount of cost (MAC). The main purpose of this paper is to give an idea about automatic shrink packaging of the final product and sorting technique which reduces the overall packaging and sorting time and also increases productivity. In this project a PLC based low-cost automation cell will be developed for industry. This automation cell combines two different types of work in one frame. One is shrinking packaging of final products and another one is sorting which is done by measuring the size of the product. The purpose of combining two different types of work in frame is to reduce the overall production time. Pneumatic system introduced here for sorting purpose. This pneumatic system works faster than an electric pusher which finally reduces the sorting time. This pneumatic system is also safe from fire hazard where there is a high chance of fire hazard in electric pusher. Sorting is done here by using a double acting cylinder acting as a pneumatic pusher and this cylinder is controlled by a 5/2 Solenoid valve. Here Sorting is done after finishing the packaging of the final product. To perform different tasks in one frame it will be helpful for industry because both labor cost and time will be reduced as well as increased the production rate of industry. By using the PLC whose model name is Siemens S7-200 and using the Micro-WIN software for making the ladder diagram, the entire system will be controlled. The experimental findings demonstrate that the system has high sorting accuracy, is reliable, and satisfies the design specifications.